Anthelmintic activity of zizyphus jujuba mill & lamk. - VEERESH,; KAMBHOJA S, (International Journal of Pharma and Bio Sciences, 2011)
Zizyphus jujuba Mill & Lamk. Is also called as Baer tree, belongs to the family Rhamnaceae. The dried bark was powdered and extracted with various solvents by successive soxhlet hot extraction process with increasing order of polarity. On phytochemical investigation, the methanol extract and aqueous extract has shown steroids, flavonids and tannins. The drug was screened for anthelmintic activity on adult earthworms Phertima posthuma, using piperazine citrate as standard drug. Both methanol and aqueous extract showed significant anthelmintic activity compared to standard drug Piperazine citrate.